Natural selection fluctuates at an extremely fine spatial scale inside a wild population of snapdragon plants. (1st October 2021) - Marrot, Pascal; Latutrie, Mathieu; Piquet, Jésaëlle; Pujol, Benoit
Abstract: Spatial variation in natural selection is expected to shape phenotypic variation of wild populations and drive their evolution. Although evidence of phenotypic divergence across populations experiencing different selection regimes is abundant, investigations of intrapopulation variation in selection pressures remain rare. Fine‐grained spatial environmental heterogeneity can be expected to influence selective forces within a wild population and thereby alter its fitness function by producing multiple fitness optima at a fine spatial scale. Here, we tested this hypothesis in a wild population of snapdragon plants living on an extremely small island in southern France (about 7500 m 2 ). We estimated the spline‐based fitness function linking individuals' fitness and five morphological traits in interaction with three spatially variable ecological drivers. We found that selection acting on several traits varied both in magnitude and direction in response to environmental variables at the scale of a meter. Our findings illustrate how different phenotypes can be selected at different locations within a population in response to environmental variation. Investigating spatial variation in selection within a population, in association with ecological conditions, represents an opportunity to identify putative ecological drivers of selection in the wild.